IMPLEMENTASI LITERASI DIGITAL DI SEKOLAH DASAR: STUDI TENTANG KESIAPAN, TANTANGAN, DAN PELUANG - Fitriani, Fitriani; Rukli, Rukli (Elementar : Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the implementation of digital literacy in elementary schools, particularly at MI Al Wahdah in Baubau City, by examining the aspects of readiness, application, challenges, and opportunities within the context of the Merdeka Curriculum. The research employed a descriptive qualitative method, with data collected through observation, semi-structured interviews, and documentation. The research subjects included the school principal, classroom teachers, and third-grade students. Research instruments consisted of interview guidelines, observation sheets, and documentation of digital learning activities. Data validity was ensured through source and technique triangulation, while data were analyzed using Miles and Huberman's interactive model, including data reduction, data display, and conclusion drawing. The results showed that school readiness was reflected in the availability of basic digital tools and the principal’s initiative in supporting teacher training. The challenges identified included limited infrastructure, varying levels of digital literacy among teachers, and the lack of parental involvement in supporting students during digital learning. Meanwhile, opportunities for development were seen in the teachers’ enthusiasm for innovation, support from external training programs, and the availability of digital learning media that could be optimized. This study recommends strengthening collaboration among stakeholders to support the sustainable implementation of digital literacy.